Analysis of Investment Decisions on LQ45 Stock by Using Moving Average Convergence Divergence (MACD) and Bollinger Bands Indicators Period January 2023 – February 2025 - Cynthia Java Al Maduri; Tri Kunawangsih Purnamaningrum; Pardomuan Sihombing (International Journal of Economics Accounting and Management, 2025)
The Indonesian capital market plays a crucial role in economic growth, with the LQ45 index representing large-cap stocks with high liquidity. This study aims to evaluate the effectiveness of the Moving Average Convergence Divergence (MACD) and Bollinger Bands technical indicators in making investment decisions on stocks during the period from January 2023 to February 2025. The research method used is descriptive qualitative, with visual analysis of price movements from 11 LQ45 stocks. The findings indicate that the combination of MACD and Bollinger Bands produces fairly accurate buy and sell signals, especially when used simultaneously. These findings provide a solid foundation for investors to formulate practical and applicable strategies based on technical analysis. Furthermore, this study contributes to the literature on the reliability of technical signals in the Indonesian stock market.